143k views
5 votes
Solve and show how you did: -2x + (12 - 9) = 2 + 9 + 2x

User Oztaco
by
5.0k points

1 Answer

1 vote
Remove parentheses
-2x + 12 - 9 = 2 + 9 + 2x

Simplify -2x + 12 -9 to -2x + 3
-2x + 3 = 2 + 9 + 2x

Simplify 2 + 9 + 2x to 2x + 11
-2x + 3 = 2x + 11

Add 2x to both sides
3 = 2x + 11 + 2x

Simplify 2x + 11 +2x to 4x + 11
3 = 4x + 11

Subtract 11 from both sides
3 - 11 = 4x

Simplify 3 - 11 to - 8
-8 = 4x

Divide both sides by 4
-8/4 = x

Simplify 8/4 to 2
-2 = x

Switch sides
x = -2
User Teodor Anton
by
5.1k points